(untitled) (Global Journal of Science Frontier Research, 2019)
In this paper, we obtained some best proximity point results for continuous proximal βquasi contractive mappings in the setting of two metrics space. We illustrate our main theorem with an example. As application, we establish several results on existence and uniqueness of fixed points in complete metric spaces.